Pendidikan Busana Muslimah Untuk Suku Baduy: Analisis Kebutuhan dan Tantangan - Ria Indriati; Chaira H Saidah Yusrie; Riyanto (Transformasi Manageria Journal of Islamic Education Management, 2024)
This research aims to be an input for the community, especially Muslim women in the Outer Baduy tribe community in the Dangka area, Banten Province, Indonesia, to be taken into consideration in choosing and wearing Muslimah clothing that is in accordance with Islamic law but can be adjusted and harmonised without leaving the characteristics of the customs and culture of the Baduy tribe, including by: (1) Assisting in providing solutions that are in accordance with the needs of Muslimah clothing for the Baduy community. (2) Providing useful information for the development of Muslimah fashion education that is adjusted to the customs and culture of the Baduy Tribe. (3) Provide a better understanding of the challenges faced in the development of Muslimah fashion education for Baduy Tribe. (4) Providing recommendations that can be used to overcome the challenges faced in the development of Muslimah fashion education for the Baduy Tribe. (5) Adding awareness in the community about the importance of Muslimah fashion education that can be adjusted to the customs and culture for the Baduy community. (6) To be a reference for further development of Muslimah fashion education in the context of Baduy Tribe and other similar contexts. (7) Providing benefits in aspects such as community development, community empowerment, expansion of Muslimah fashion education well.